Red-hot cold call selling : prospecting techniques that pay off - Goldner, Paul S. (AMACOM, 1995)
Whether you're a seasoned salesperson or a professional selling your own services, you'll get better results with Red-Hot Cold Call Selling. It's filled with valuable strategies and techniques for developing a complete selling system that works. You'll learn to properly define your target market - and stop squandering money and time on unfocused prospecting; free yourself of the cold-call jitters and render yourself rejection-proof; dissect the cold call and develop a personalized script that works best for you; get past secretaries, administrative assistants, and even that nemesis of the telecommunications age: voice mail; and have prospects come to you by generating your own public relations, newsletters, and more.